2016
DOI: 10.1080/07391102.2016.1185381
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional annotation of miRNAs in anti-inflammatory plant and their cross-kingdom regulation in Homo sapiens

Abstract: MicroRNAs (miRNAs) are newly discovered non-coding small (~17-24 nucleotide) RNAs that regulate gene expression of its target mRNA at the post-transcriptional levels. In this study, total 12,593 ESTs of Curcuma longa were taken from database of expressed sequence tags (dbEST) and clustered into 2821 contigs using EGassembler web server. Precursor miRNAs (pre-miRNAs) were predicted from these contigs that folded into stem-loop structure using MFold server. Thirty-four mature C. longa miRNAs (clo-miRNAs) were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Besides various in vitro and in vivo studies, two recent in silico analyses also strengthened cross-kingdom gene regulation [39,40]. In these reports, the miRNAs were predicted from the available EST datasets of important medicinal plants happy tree (Camptotheca acuminata) [39] and Curcuma longa [40]. In happy tree, the identified miRNAs were predicted to be targeting the cancer associated genes of human and their regulation of expression.…”
Section: In Silico Analysis Of Exogenous Plant Mirnasmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides various in vitro and in vivo studies, two recent in silico analyses also strengthened cross-kingdom gene regulation [39,40]. In these reports, the miRNAs were predicted from the available EST datasets of important medicinal plants happy tree (Camptotheca acuminata) [39] and Curcuma longa [40]. In happy tree, the identified miRNAs were predicted to be targeting the cancer associated genes of human and their regulation of expression.…”
Section: In Silico Analysis Of Exogenous Plant Mirnasmentioning
confidence: 97%
“…The stability of miRNAs is due to unique sequence and high GC content in addition to its methylation [35]. Besides various in vitro and in vivo studies, two recent in silico analyses also strengthened cross-kingdom gene regulation [39,40]. In these reports, the miRNAs were predicted from the available EST datasets of important medicinal plants happy tree (Camptotheca acuminata) [39] and Curcuma longa [40].…”
Section: In Silico Analysis Of Exogenous Plant Mirnasmentioning
confidence: 99%
“…So far, compelling evidence has demonstrated that plant miRNAs are present in human/animal plasma and these miRNAs usually belong to evolutionary conserved families (Vaucheret and Chupeau, 2012; Zhang et al, 2012; Liang et al, 2014; Yang et al, 2015a; Yang et al, 2015b; Cavalieri et al, 2016). Plant miRNAs not only from edible plant species (rice, cabbage, broccoli, watermelon, soybean, strawberry, olive) but also from model (Arabidopsis, poplar) and medicinal plants (Moringa, honeysuckle, turmeric, ginger) had been evaluated for their potential trans -kingdom transfer (Zhang et al, 2012; Liang et al, 2014; Zhou et al, 2015; Cavalieri et al, 2016; Chin et al, 2016; Pirrò et al, 2016; Liu et al, 2017; Sharma et al, 2017; Minutolo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Later on, the levels of other plant‐derived miRNAs, such as miR172 from Brassica oleracea ; MIR2911 from the honeysuckle; mol‐miR166i, mol‐miR393c, and mol‐miR168a from Moringa oleifera ; and clo‐mir‐14 from Curcuma longa were experimentally determined by quantitative real‐time PCR (qRT‐PCR). These miRNAs were found to regulate inflammation, immune tolerance, tumour necrosis factor alpha (TNF‐α) expression, antiviral activity against influenza, and inhibition of SIRT1, which is involved in the regulation of human prostate, colon cancer, and acute myeloid leukemia in humans . Further, Chin et al recently reported that the plant‐derived miR159 can inhibit cancer growth in mice.…”
Section: Introductionmentioning
confidence: 99%